Empowerment of Women Through Microfinance - A Case Study of Ranga Reddy District, Andhra Pradesh - Mahendra, M. V. S. (Indian Journal of Finance, 2011)
Microfinance in India is dominated by the Self Help Group -Bank Linkage Programme as an effective tool for poverty alleviation. Micro Finance Institutions (MFIs) in India provide financial assistance to individuals or eligible clients either directly or through a group mechanism. Most of the MFIs are in the form of Non-Government Organisations (NGOs), while there are some company MFIs. The NGO-MFIs may be expected to ensure that they provide or facilitate timely and adequate credit to the vulnerable groups at an affordable cost, i.e. in an inclusive manner. Dr. Rangarajan committee has defined financial inclusion as "the process of ensuring access to financial services and timely and adequate credit where needed by vulnerable groups such as weaker sections and low income groups at an affordable cost". The present paper attempts at the role of micro finance for women empowerment. It deals with the socio economic conditions of the members of the self help group. The study mainly focuses on the members of self help group in Ranga Reddy District of Andhra Prasdesh. Based on the primary study, it has been observed that the members of the self help group were largely benefitted and their status of living has increased. The study has been conducted in the three divisions of Ranga Reddy district. It particularly focuses on women and their status after becoming the members of the self help group.